Study on Technical Challenges of Maintenance Vehicle Trains (MVTs) for Construction Phase in ECRL Project - Ahmad Shukri, Fadhlan Syakirin; Yahya, Musli Nizam; Nazaruddin, Siti Nina Nadia (Progress in Engineering Application and Technology, 2025)
The East Coast Rail Link (ECRL), spanning 665 km across Peninsular Malaysia, is a key national infrastructure project. A crititical component in its construction involves the use of Maintenance Vehicle Trains (MVTs),  including tamping machines, ballast regulators, and dynamic stabilizers. However, the MVTs face significant operational challenges due to  Malaysia’s tropical environment, such as heavy rainfall, humidity, dust  accumulation, and the project’s reliance on foreign spare parts, particularly from China. These issues have led to frequent breakdowns and project delays. This study aims to identify these technical challenges and offer practical solutions, addressing a gap in current literature regarding localized operational issues of MVTs in large-scale railway projects. The research employed a structured questionnaire distributed to 50 technical personnel from Malaysia Rail Link (MRLSB) and China Communications Construction Company (CCCC) who are directly involved in MVT operations. Respondents provided feedback on environmental, mechanical, and supply chain challenges, as well as mitigation strategies. Quantitative analysis was performed using descriptive statistics and reliability testing. Findings confirmed that environmental factors, mechanical wear from extended use, and foreign spare part dependency are the most critical challenges affecting MVT reliability and project progress. The study highlights three practical mitigation strategies most supported by respondents: (1) frequent lubrication of moving parts, (2) regular maintenance of components exposed to dust and rainfall, and (3) developing local suppliers for critical components. These strategies aim to improve MVT reliability and support smoother project execution for ECRL and similar rail projects.